Effect of the load level in the fire resistance of composite slab with steel decking - Balsa, Carlos (2020)
The composite slab with steel decking is widely used in every type of buildings and requires fire resistance, in accordance to regulations and standards. The concrete is usually reinforced with a steel mesh on the top and may also be reinforced using individual rebars. The fire assessment should consider the criterion for stability (R), Integrity (E) and insulation (I). The scope of this investigation concerns the fire rating for the R and I criteria. Numerical simulations with finite elements were developed, using ANSYS, to find out the thermal and mechanical effects of standard fire exposure. The fire resistance criteria for loadbearing (R) depends on the maximum displacement (D) or on the rate of displacement (dD/dt), while the fire resistance for insulation depends on the maximum or average temperatures in the unexposed side. A literature review from different investigations is presented [1] [2]. The results of the numerical simulation are compared with experimental results to validate the model [3]. The results are also compared with the simplified method proposed by Eurocode 4-part 1.2 [4].